2016
DOI: 10.1111/jomf.12377
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Men's Childbearing Intentions in Father Involvement

Abstract: An expanding body of research has investigated factors that influence fathers’ involvement with their children. Generally overlooked has been the role of pregnancy intentions on men’s fathering behaviors. In this study, the authors used nationally representative data from men interviewed in the 2002 and 2006–2010 National Survey of Family Growth to examine relationships between fathers’ pregnancy intentions and multiple aspects of their parental involvement. Using propensity score methods to control for confou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 53 publications
2
45
0
3
Order By: Relevance
“…For both men and women, relationship struggles that both contributed to, and were exacerbated by, the unintended pregnancy can translate into a lack of partner support and place a greater share of the parenting and childcare burden on one parent. This study is among the first to highlight consequences experienced by men (Lindberg et al, 2016; Bronte-Tinkew et al, 2007; Bronte-Tinkew et al, 2009; Edin and Nelson, 2013). Future research to delve further into how men and women differentially experience and manage unintended childbearing is warranted.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…For both men and women, relationship struggles that both contributed to, and were exacerbated by, the unintended pregnancy can translate into a lack of partner support and place a greater share of the parenting and childcare burden on one parent. This study is among the first to highlight consequences experienced by men (Lindberg et al, 2016; Bronte-Tinkew et al, 2007; Bronte-Tinkew et al, 2009; Edin and Nelson, 2013). Future research to delve further into how men and women differentially experience and manage unintended childbearing is warranted.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, positive effects are to be expected — having a child can feel like a miraculous experience, bringing unanticipated joy and meaning to one's life. Indeed, research has shown that women and men experiencing unintended childbearing often express happiness about the birth, and some find meaning and motivation in their lives as a result (Hartnet, 2012; Lindberg and Kost, 2014a; Lindberg et al, 2016; Aiken et al, 2015). Recognizing that positive effects of unintended childbearing exist alongside negative ones could help to refine the messages of future campaigns aimed at reducing unintended pregnancy as well as situating motherhood and/or fatherhood resulting from unintended pregnancy as an opportune time to engage parents in educational or work programs that support positive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that parents engage in effective parenting strategies, as this is important to adolescent development (Niaraki & Rahimi, 2013). Fathers and their love are crucial to the family unit (Choi & Jackson, 2011), and the involvement of fathers in raising their children is linked to more positive outcomes for their children's health and well-being (Lindberg, Kost, & Maddow-Zimet, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to read this work in the light of 'gender balance' arguments in ECEC settings and the very similar questions that are asked in this context about the presence and absence of male teachers. In the 1990s and early part of the millennium, much research on fathers was focused on levels of paternal involvement; the quantity of time spent in childcare (Lindberg et al, 2016;Cabrera et al, 2014;Lamb, 2010). Then researchers moved to a concern with the quality of fathering practices emphasising that it what fathers do when they are present that makes a difference to outcomes for children (Lamb, 2010;Parke and Brott;Honig;2009).…”
Section: Theoretical Background On Gender Balance and Gender Flexibilmentioning
confidence: 99%